Targeting Drp1 and mitochondrial fission for therapeutic immune modulation. (August 2019) - Simula, Luca; Campanella, Michelangelo; Campello, Silvia
Graphical abstract: Abstract: Mitochondria are dynamic organelles whose processes of fusion and fission are tightly regulated by specialized proteins, known as mitochondria-shaping proteins . Among them, Drp1 is the main pro-fission protein and its activity is tightly regulated to ensure a strict control over mitochondria shape according to the cell needs. In the recent years, mitochondrial dynamics emerged as a new player in the regulation of fundamental processes during T cell life. Indeed, the morphology of mitochondria directly regulates T cell differentiation, this by affecting the engagment of alternative metabolic routes upon activation. Further, Drp1-dependent mitochondrial fission sustains both T cell clonal expansion and T cell migration and invasivness. By this review, we aim at discussing the most recent findings about the roles played by the Drp1-dependent mitochondrial fission in T cells, and at highlighting how its pharmacological modulation could open the way to future therapeutic approaches to modulate T cell response.